2017
DOI: 10.1002/glia.23268
|View full text |Cite
|
Sign up to set email alerts
|

Regional oligodendrocytopathy and astrocytopathy precede myelin loss and blood–brain barrier disruption in a murine model of osmotic demyelination syndrome

Abstract: The osmotic demyelination syndrome (ODS) is a non-primary inflammatory disorder of the central nervous system myelin that is often associated with a precipitous rise of serum sodium concentration. To investigate the physiopathology of ODS in vivo, we generated a novel murine model based on the abrupt correction of chronic hyponatremia. Accordingly, ODS mice developed impairments in brainstem auditory evoked potentials and in grip strength. At 24 hr post-correction, oligodendrocyte markers (APC and Cx47) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(95 citation statements)
references
References 52 publications
7
88
0
Order By: Relevance
“…Following the development of a mouse model of ODS induced by the abrupt correction of a chronic hyponatremia, analysis of fine structural aspects has been able to verify some neuropathologic damages previously described at the EM level (Bouchat et al 2018). Many histopathologic similarities were found compared with the ODS rat model (Rojiani et al 1994) and the human case studies (Powers and McKeever 1976).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Following the development of a mouse model of ODS induced by the abrupt correction of a chronic hyponatremia, analysis of fine structural aspects has been able to verify some neuropathologic damages previously described at the EM level (Bouchat et al 2018). Many histopathologic similarities were found compared with the ODS rat model (Rojiani et al 1994) and the human case studies (Powers and McKeever 1976).…”
Section: Discussionmentioning
confidence: 85%
“…ODS 48 H Astrocytes from Caudate Putamen In order to strengthen these findings, the surveys of striatal astrocytes morphology found that no demyelinating lesions or cellular damages were noticed in the caudate putamen using light microscopy (Bouchat et al 2018). To further confirm these data, our observations obtained in and around the ODS thalamus lesions were compared with a morphologically undamaged The plus sign indicates present; the minus sign indicates absent central nervous system (CNS) area.…”
Section: Hn Astrocytesmentioning
confidence: 83%
See 3 more Smart Citations